Development and in vitro characterization of metronidazole loaded chitosan microspheres for delivery to periodontal pocket - Preeti K. Suresh, Mahendra Kumar Dewangan (Journal of Applied Pharmaceutical Science)
The aim of the present work was to develop drug delivery system for localized controlled release of metronidazole following insertion into and/or around the periodontal pocket. This would ensure increased local drug concentration at the periodontal site to maintain an effective concentration over an extended period of time and a decrease in superfluous distribution of the drug to other body organs with a subsequent decrease in side effects. In the present work, metronidazole loaded chitosan microspheres were prepared by external gelation technique using tripolyphosphate as the cross-linker. The drug to polymer ratio was chosen at three levels: 1:4, 1:5 and 1:6 (by weight) and tripolyphosphate concentration also at three levels: 6, 12 and 18 (%). The microspheres were characterized for surface morphology, particle size, drug entrapment efficiency, swelling, erosion, bioadhesion and drug release profile. Nearly spherical, rough and porous particles (size ~ 800 µm) were obtained. Drug entrapment efficiency was found to be in the range of 60-75%. Percentage swelling, erosion and bioadhesion ranged from 10-25%, 5-15% and 43-59% respectively. The results indicated that formulation of metronidazole in chitosan microspheres could be utilized as a potential drug delivery system to periodontal pocket.
Keywords: Biodegradable polymer, external gelation, local delivery, microparticles, mucoadhesive, periodontitis.